+0  
 
0
216
2
avatar

ax^2+bx+c=0 Solve for x.

Guest Mar 22, 2015

Best Answer 

 #1
avatar+80933 
+10

If we do this correctly....we will arrive at a familiar formula....let's see...

ax^2+bx+c=0   subtract c from both sides

ax^2 + bx  = -c       divide through by a

x^2 +(b/a)x = -c/a     complete the square on x

x^2 + (b/a)x + [b^2] / [4a^2]  = -c/a + [b^2] / [4a^2]     factor the right side....get a common denominator on the left

[x + (b/2a)]^2  = [b^2 - 4ac] / [4a^2]   take the square roots of both sides

x + (b/2a)  = ±√[b^2 - 4ac]/[2a]    subtract (b/2a) from both sides

x = (-b±√[b^2 - 4ac]) / [2a]

Voila!!!....we have the Quadratic Formula..... !!!!

 

  

CPhill  Mar 22, 2015
Sort: 

2+0 Answers

 #1
avatar+80933 
+10
Best Answer

If we do this correctly....we will arrive at a familiar formula....let's see...

ax^2+bx+c=0   subtract c from both sides

ax^2 + bx  = -c       divide through by a

x^2 +(b/a)x = -c/a     complete the square on x

x^2 + (b/a)x + [b^2] / [4a^2]  = -c/a + [b^2] / [4a^2]     factor the right side....get a common denominator on the left

[x + (b/2a)]^2  = [b^2 - 4ac] / [4a^2]   take the square roots of both sides

x + (b/2a)  = ±√[b^2 - 4ac]/[2a]    subtract (b/2a) from both sides

x = (-b±√[b^2 - 4ac]) / [2a]

Voila!!!....we have the Quadratic Formula..... !!!!

 

  

CPhill  Mar 22, 2015
 #2
avatar+91436 
0

Thanks Chris :)

Melody  Mar 22, 2015

2 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details